Pernikahan Terpaksa di Era Milineal Perspektif Ulama Mazhab; Studi Kasus di Kecamatan Sinjai Timur - Ikrawati Nur; Lukman Arake (Universitas Islam Negeri Alauddin Makassar, 2021)
The purpose of this study is to find out how forced marriage is in the millennial era from the perspective of mazhab scholars (a case study in the eastern Sinjai sub-district)? 1) What are the implications of marriage? 2) What are the impacts of forced marriage for forced married couples? 3) What are the views of the mazhab scholars on forced marriages that occurred in the East Sinjai sub-district? In the problem above the author using a normative theological approach (Islamic law) and a sociological approach. This research is classified as Field Research using a qualitative approach that focuses on the practice of forced marriage in the eastern Sinjai sub-district, the data used by the author is taken from the results of observations and interviews using the collection method according to the classification. The results of this study show the conclusion that can be drawn from the results of this study is where a child can choose his own life partner, parents only have to act as advisers to say what is good and what is not. Any risk that will occur in the future for the marriage that occurs is already a consequence that must be borne by the child. Even if you have to be forced to marry, give a logical reason. The factors causing the practice of forced marriage are: Reply Factors, Economic Factors, Religious Factors, Educational Factors